REPRODUKSI RUANG KOMERSIL ATAS RUANG PERMUKIMAN DI JALAN BUDI UTOMO KABUPATEN MIMIKA - Bae, Irfan; Mujiati, Mujiati; Ngutra, Risky Novan (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2024)
The reproduction of commercial space over residential space is one of the fascinating phenomena occurring in the development of regions and cities, making it an intriguing subject for scientific research. This study aims to analyze and understand the implications for the development of spatial zoning patterns, specifically on Budi Utomo Street in Mimika Regency. This is evidenced by the initiative of business actors (Capital) to develop urban infrastructure, resulting in irregular patterns. This has motivated the emergence of unplanned spatial areas and cities, affecting spatial patterns, transportation, city character, and urban development directions. This study provides an overview of how commercial space can be reproduced over residential space on Budi Utomo Street and how to interpret the issues that arise in the context of spatial utilization patterns in regions and cities, including urban planning directions that consider local wisdom. It employs both qualitative and quantitative methods in descriptive analysis using cross-tabulation or Likert scale approaches, while also referencing several theoretical studies on regional and urban planning sciences.